An Analysis of Characterization in Movie “Moana” - Pebrianti, Kadek Dewi (Institut Pariwisata dan Bisnis Internasional, 2023)
This research focuses on “An Analysis of characterization in the movie Moana”. It aims to analyze the characterization of character in Moana movie. The data were taken from the characters in Moana movie and were analyzed to reveal what characterization used to describe the character and what types of character is found in the movie based on theory by Kenney (1966) and theory of characterization by Murphy (1972). The data source of this research was the movie “Moana”. The researcher collects the data using qualitative research method. Based on the result of the analysis, there are some characters that can be categorized into their characterization. The research concluded that there are three types of characters found in Moana movie such as main character, second character and supporting character. Moana being the main character, Maui is second character, and Villager, Heihei, Te Fiti, Tui, Sina, Gramma Tala and Tamatoa supporting characters. Besides that, to support this analysis about characterization there are nine methods of characterization such as personal description, character as seen by another, speech, past lives, conversation of others, reactions, direct comment, thought, and mannerism. But not all of the characters use all methods of characterization.